2020
DOI: 10.1021/acsaem.0c01070
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Ether Solvent and Anion Coordination on Electrochemical Behavior in Calcium Battery Electrolytes

Abstract: The emergence of magnesium and calcium batteries as potential beyond Li ion energy storage technologies has generated significant interest into the fundamental aspects of alkaline earth metal cation coordination in multivalent electrolytes and the impact of coordination on application-critical electrolyte properties such as solubility, transport, and electrochemical stability. Understanding these details in calcium electrolytes is of immediate importance due to recent, unprecedented demonstrations of reversibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
140
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(155 citation statements)
references
References 46 publications
14
140
1
Order By: Relevance
“…Ca electrolytes were prepared by dissolving CMC into the weakly coordinating solvents, which enabled the dissociation of Ca salts 37 39 . As the weakly coordinating solvents, THF, DME, and a mixture of DME/THF (1:1, v/v) were selected, and the solubilities of CMC were evaluated by ICP-OES using saturated solutions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ca electrolytes were prepared by dissolving CMC into the weakly coordinating solvents, which enabled the dissociation of Ca salts 37 39 . As the weakly coordinating solvents, THF, DME, and a mixture of DME/THF (1:1, v/v) were selected, and the solubilities of CMC were evaluated by ICP-OES using saturated solutions.…”
Section: Resultsmentioning
confidence: 99%
“…S8 ). Considering the influence of the type of ether solvent and anion coordination on Ca, the incompetency of these electrolytes arises due to the coordination of Ca with diglyme and triglyme being stronger than that of Ca with DME and THF 37 .
Figure 2 ( a ) Cyclic voltammograms of Ca plating/stripping after conditioning cycles at 20 mV s −1 with a three electrode setup using Au as the working electrode and Ca as the reference and counter electrodes at room temperature.
…”
Section: Resultsmentioning
confidence: 99%
“…14,15 As a result, the large size of Ca 2+ can act to drive anionic association within the electrolytic solution, which can inhibit rapid transport of ions or induce anion reduction at the electrode surface. 10,16,17 In fact, our most recent work combined spectroscopic analysis with MD simulations to characterize ion association tendencies in ethereal-CaTFSI2 electrolytes in which we found the solvent:Ca 2+ coordination strength to increase as 2-MeTHF < THF < G1 < G2 < G3 with clear evidence of Ca 2+ -TFSI contact ion-pairs even with G2 solvation. 10 These factors all reveal the critical importance of the Ca 2+ solvation environment for electrochemical deposition and stripping of Ca metal.…”
Section: Introductionmentioning
confidence: 95%
“…9 However, similar measurements using triglyme (G3), a longer linear ethereal solvent, provided negligible success. 10 While many of these electrolyte compositions provide promising steps towards reversible Ca 2+ electrochemistry, each exhibits susceptibility to decomposition leading to the formation CaF2 layers and organic byproducts on the electrode surface that inhibit calcium diffusion. [8][9][10] For example, a comparison of the compositions of calcium deposits by energy dispersive X-ray analysis revealed that using THF as the supporting solvent leads to greater relative F content while using G1 or G2 leads to greater relative O content.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation